PELATIHAN TENTANG MODEL-MODEL PEMBELAJARAN BAHASA INDONESIA DI SD PADA GURU-GURU SD DI KECAMATAN TOMOHON TENGAH - Neltje Kambey (LPPM UNIMA, 2016)
One of the powerful thing of Indonesia in developing this countryis Indonesian language. It is a tool of communication formally used for all the society and to all institution in Indonesia. The instruction of Indonesia language implemented in all level of education in Indonesia started from Elementary till the higher education. The primary school teacher should create an interesting condition in language instruction to make students enjoyable in learning in order to improve both of their love as well as their ability in Indonesia language. To reach this purposes, the teachers need to know, to master, to have skill in determine the appropriate models of teaching in Indonesia languange, and also have ability to apply them in instruction. The teacher really need to be trained the inovative models of teaching so that they can understand about it. They also need to work together with their collegous to help each other in arranging the lesson plan and to simulate among them. This activity gives them opportunity to repair their conventionl instruction to the new one for the better students as well as the better Indonesian in the future.